2016
DOI: 10.1007/s00059-016-4422-8
|View full text |Cite
|
Sign up to set email alerts
|

Kardiovaskuläres Risiko unter Androgendeprivationstherapie zur Behandlung des hormonabhängigen Prostatakarzinoms

Abstract: Prostate cancer patients with either cardiovascular disease or an increased risk of experiencing a cardiovascular event undergoing ADT should be preferentially treated with GnRH antagonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Observational, retrospective studies using real-world databases have shown that GnRH antagonists may have a better CV risk profile than GnRH agonists in patients with and without a history of CV events. [21][22][23][24] An overview of CV risk associated with the use of ADTs, specifically a comparison between a GnRH agonist and antagonist and between ADT use and non-ADT use, is provided in Table 5. Data from the Margel study 13 and the HERO study 14 showed that antagonists were associated with a several-fold lower risk of CV events than agonists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Observational, retrospective studies using real-world databases have shown that GnRH antagonists may have a better CV risk profile than GnRH agonists in patients with and without a history of CV events. [21][22][23][24] An overview of CV risk associated with the use of ADTs, specifically a comparison between a GnRH agonist and antagonist and between ADT use and non-ADT use, is provided in Table 5. Data from the Margel study 13 and the HERO study 14 showed that antagonists were associated with a several-fold lower risk of CV events than agonists.…”
Section: Discussionmentioning
confidence: 99%
“…It states that ADT for prostate cancer appears to increase the risk of cardiovascular events, although GnRH antagonists may be associated with a lower risk of CV events than GnRH agonists. The GnRH antagonists may have a lower risk of CV events compared with agonists, as evidenced from randomized controlled trials (RCTs), 13–15 meta‐analysis of data from prostate cancer trials with GnRH analogs, 16–20 and real‐world data, 21–24 although not all studies have been consistent in these findings (Table 1). 25–27 …”
Section: Risk In Rcts With Gnrh Agonists and Gnrh Antagonist Referenc...mentioning
confidence: 99%
See 1 more Smart Citation
“…ADT increases cardiovascular morbidity in men with PCa ( 16 ). Since the potentially different effects of GnRH agonists and antagonists on CVD risk are still controversially discussed ( 17 20 ), one aspect of this analysis was the comorbidity rate, in particular CVD comorbidity, among GnRH agonists and the antagonist. However, due to the small number of patients in the degarelix cohort, the results do not allow any conclusion and more evidence is needed.…”
Section: Discussionmentioning
confidence: 99%